Argumentação e persuasão: O sermão da sexagésima do Padre Antônio Vieira - Melo, Sangia de (2005)
This dissertation has as objctive analyse the sixtieth Sermon, expliciting the argumentation and persuasion devices with support in two main artifice linguistics: the metaphor and allegory. It divides itself into three chapters: The rethoric of Sermon, The archictecture of sixtieth Sermon and Vieira´ s oracle Art. It was pronounced at Lisbon Real Chapel, the sixtieth Sermon is considered an example preach. In it, Vieira confirms his missionary, visionary and politician functions. His subject is religious and dedicates to transmit the knowledge of faint and moving the wills, in order to the behaviours and options of life correspond the cristian doctrine. We found into sermon, conative, metal-linguistics and poetical functions of language, as well new syntaxes, combinations and articulations used for keeping attention from his listeners with intention to convert and conduct them the action